1996
DOI: 10.1016/s0092-8674(00)81812-7
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Angiopoietin-1, a Ligand for the TIE2 Receptor, by Secretion-Trap Expression Cloning

Abstract: TIE2 is a receptor-like tyrosine kinase expressed almost exclusively in endothelial cells and early hemopoietic cells and required for the normal development of vascular structures during embryogenesis. We report the identification of a secreted ligand for TIE2, termed Angiopoietin-1, using a novel expression cloning technique that involves intracellular trapping and detection of the ligand in COS cells. The structure of Angiopoietin-1 differs from that of known angiogenic factors or other ligands for receptor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

31
1,233
4
41

Year Published

1998
1998
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,809 publications
(1,309 citation statements)
references
References 31 publications
31
1,233
4
41
Order By: Relevance
“…Fibrinogen and is composed of two each of three homologous polypeptide chains ( 2, 2, 2) and is an essential protein for blood clotting. Tenascins take responsibility for cell adhesion, whereas angiopoietins can stimulate angiogenesis [9]. The precise functions of the fibrinogen-like domain-containing proteins have not been fully elucidated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fibrinogen and is composed of two each of three homologous polypeptide chains ( 2, 2, 2) and is an essential protein for blood clotting. Tenascins take responsibility for cell adhesion, whereas angiopoietins can stimulate angiogenesis [9]. The precise functions of the fibrinogen-like domain-containing proteins have not been fully elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…HFREP-1/LFIRE-1 belongs to fibrinogen superfamily, whose members share a common fibrinogen-like domain at their carboxy-termini [7]. They might act as molecular facilitator participating in the proliferation and adhesion of cells, angiogenesis and carcinogenesis [8][9][10]. Northern blot assay revealed that hfrep-1/lfire-1 was exclusively expressed in normal rat liver and two human hepatoma cell lines, HepG2 and PLC/PRF/5 [7].…”
Section: Introductionmentioning
confidence: 99%
“…15 Angiopoietins (Ang1-4) are ligands for the tyrosine kinase receptor Tie2. [16][17][18] Ang1 activates Tie2 signaling pathways and promotes the recruitment of pericytes and smooth muscle cells to the developing vessels 16,19 and contributes to tumor dissemination and metastasis. 20 Ang2, on the contrary, functions in a context-dependent manner as an antagonist promoting either blood vessel growth or regression depending on the levels of other growth factors, such as VEGF-A.…”
Section: Introductionmentioning
confidence: 99%
“…5 showing lack of development of the endothelial lining of the heart, lack of remodeling of the primary capillary plexus to form more complex higher order branching vessels, failure of vascular invasion of neuroectoderm, and lack of recruitment of periendothelial cells. 3,4 Angiopoietin-1 (Ang1), which binds with high affinity to Tie2 and initiates phosphorylation and down stream signaling, 5 is a critical Tie2 agonist; mice deficient in Ang1 die around E12.5 and show vascular defects similar to, but less severe than, those seen in Tie2-deficient mice. 6 Angiopoietin-2 (Ang2) also binds with high affinity to Tie2, but does not stimulate its phosphorylation in cultured endothelial cells.…”
Section: Introductionmentioning
confidence: 99%